2017
DOI: 10.1111/jvh.12709
|View full text |Cite
|
Sign up to set email alerts
|

Overt and occult hepatitis B virus infection among community children in Northwest China

Abstract: Summary Although a universal newborn hepatitis B (HB) immunization programme has been implemented in China, hepatitis B virus (HBV) breakthrough infection, including HB surface antigen (HBsAg)‐positive infection and occult HBV infection (OBI), still occurs during infancy or childhood. Obtaining the actual prevalence of HBV infection in general children is important for preventing and controlling the spread of HB. Accordingly, we investigated the prevalence of overt infection and OBI in community children and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…Interestingly we did not find any occult hepatitis B in the children enrolled in our study. In a recent study conducted in China, a low rate of occult hepatitis B (1.26%) was observed in 1.192 community children [28]. Our study has some limitations: first the parents were not surveyed on the history of hepatitis B in the family.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly we did not find any occult hepatitis B in the children enrolled in our study. In a recent study conducted in China, a low rate of occult hepatitis B (1.26%) was observed in 1.192 community children [28]. Our study has some limitations: first the parents were not surveyed on the history of hepatitis B in the family.…”
Section: Discussionmentioning
confidence: 94%
“…A person with occult hepatitis B infection (OBI) has a risk of reactivation during immunosuppression and due to lack of detectable HBsAg there is an ongoing risk of transmission to others [ 4 ]. Globally, OBI is ≥8% prevalence in endemic regions and is high in populations at high risk of infection including the HIV infected or people who inject drugs [ 5 ]. A majority of people are unaware of their HBV infection, and often present with advanced disease [ 13 ], as noted in Nigeria where 5.4% of the donors had anti-HBcIg M as the only serological evidence of HBV infection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China and South East Asia, isolated anti‐HBs were reported in 6.3%–20.3% of immunocompetent blood donors with OBI 2,7–9 . Isolated anti‐HBs OBI has been also reported in immunized neonates born to HBsAg‐positive mothers and children with HBsAg‐positive parents 10–14 . When available, follow‐up of vaccinated children in these studies was relatively limited in time and often showed low and transient HBV DNA levels 11,13 .…”
Section: Introductionmentioning
confidence: 95%